(untitled) (Docentes 2.0 Journal, 2024)
The feeling of concern linked to structuring the teacher’s competency profile is not new. Still, it has recently been taken into account in higher education due to its implication on the practice and quality of teaching. The purpose of the research proposal was to establish the relationship between digital competence, pedagogical practice, and reflective practice from the participation of university teachers. It was developed under a positivist paradigm, hypothetical-deductive method, quantitative approach, non-experimental-correlational design, correlational and cross-sectional type. The sample comprised 66 teachers in the Faculty of System Engineering and Computer Science and Education of a Public University of Madre de Dios, selected by non-probabilistic means for convenience. The variables, the survey, and three questionnaires were used as instruments, duly validated by experts, and were of high reliability. The results confirmed that digital competencies and pedagogical practice have a moderate relationship; therefore, greater concern is evident to innovate the educational process. In addition, a moderate relationship was found between digital competencies and reflective practice, giving an understanding that from the reflection on teaching performance, participation and concern about the improvements in their skills are evident. Finally, the very high relationship between pedagogical practice and reflective practice was confirmed; the reflection of the practice focuses on improving the educational process.